Evaluating Artificial Intelligence’s Impact on Leadership Agility in Sustainability-Driven SMEs in MENA Amid Market Challenges - Ayoub, Stephanie (Digital Repository of Theses, 2026)
The MENA region has witnessed a growing adoption of Artificial Intelligence (AI) technologies among small and medium-sized enterprises (SMEs), particularly those driven by sustainability goals. Over the past decade, AI has become a central enabler of agility, innovation, and data-driven decision-making across industries. However, despite this technological advancement, many sustainability-oriented SMEs continue to face challenges in translating AI adoption into leadership agility and measurable performance improvement. One of the key reasons is the limited contextual understanding of how AI applications, such as automation, predictive analytics, and intelligent agents, interact with leadership behavior in resource-constrained environments. Current academic research remains fragmented, with most studies focusing on large corporations in digitally mature economies, leaving a significant gap in the MENA context. The study adopts a qualitative, capability-focused perspective, examining how AI-enabled tools shape leadership agility and sustainability-oriented decision-making, rather than empirically measuring organizational performance outcomes, which remain uneven and context-dependent across SMEs in the MENA region. This research project will investigate how AI technologies enhance leadership agility in sustainability-driven SMEs, aiming to develop a contextualized framework that links AI adoption to adaptive leadership, organizational resilience, and sustainable performance outcomes.